Parents' perceptions of HIV counselling and testing in schools : Ethical, legal and social implications - Gwandure, R; Ross, E; Dhai, A; et al (My University, 2014)
In view of the high prevalence of HIV and AIDS in South Africa, particularly among adolescents, the Departments of Health and Education have proposed a school-based HIV counselling and testing (HCT) campaign to reduce HIV infections and sexual risk behaviour. Through the use of semi-structured interviews, our qualitative study explored perceptions of parents regarding the ethico-legal and social implications of the proposed campaign. Despite some concerns, parents were generally in favour of the HCT campaign. However, they were not aware of their parental limitations in terms of the Children’s Act. Their views suggest that the HCT campaign has the potential to make a positive contribution to the fight against HIV and AIDS, but needs to be well planned. To ensure the campaign’s success, there is a need to enhance awareness of the programme. All stakeholders, including parents, need to engage in the programme as equal partners.
KM
Keywords: HIV Infections/prevention & control; Counseling; Ethics; Jurisprudence